Perspectives for the production and usage of wood chips as a source of energy in the North-West of Russia - Ovcharenko, Olga (2011)
The development of bioenergy on the basis of wood fuels has received considerable attention in the last decades. The combination of large forest resources and reliance on fossil fuels makes the issue of wood chips usage in Russia an actual topic for the analysis. The main objective of this study is to disclose the current state and perspectives for the production of wood chips and their usage as a source of energy in the North-West of Russia. The study utilizes an integrated approach to explore the market of wood chips on the basis of comprehensive analysis of documentation and expert opinions. The analysis of wood chips market was performed for eight regions of the North-West district of Russia within two major dimensions: its current state and perspectives in the nearest five years. The results of the study show a comprehensive picture of the wood chips market, including the potential for wood chips production, the specific features of production and consumption and the perspectives for the market development within the regions of the North-West district of Russia. The study demonstrated that the market of wood chips is underdeveloped in the North-West of Russia. The findings of the work may be used by forest companies for the strategic planning.